A special admixture for solid waste-based cementitious materials

By providing a special admixture for solid waste-based gelling materials, the traditional water reducing agent to solid waste-based solid waste-based base uses competitive adsorption of phosphate groups in component C and the dispersion ability of medium and long chains of components A and B, the traditional water-reducing agent to solid waste-based base is solved. The problem of poor applicability of gelling materials has achieved effective water reduction and improved working performance of concrete.

CN117105567BActive Publication Date: 2025-02-14BEIKE YUNHONG ENVIRONMENTAL PROTECTION TECH BEIJING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311079255.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-14
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

Traditional water reducing agents have poor applicability to solid waste-based gelling materials, which leads to poor working performance, large losses in slump and expansion, limiting their application.

Method used

Provided is a special admixture for solid waste-based gelling materials, and the components include 35 to 55 parts of component A, 20 to 30 parts of component B and 10 to 40 parts of component C, through competition for phosphate groups in component C. Adsorption and dispersion ability of the medium and long chains of components A and B, optimize the water reduction effect and concrete working performance.

Benefits of technology

Through preferential adsorption of phosphate groups in component C and dispersing capacity of long chains in components A and B, effective water reduction of solid waste-based gelling materials and improved concrete working performance, improving slump and Stability of scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004413727640000011
    Figure BDA0004413727640000011
  • Figure BDA0004413727640000021
    Figure BDA0004413727640000021
  • Figure BDA0004413727640000022
    Figure BDA0004413727640000022
Patent Text Reader

Abstract

The present invention discloses a special admixture for solid waste-based cementitious materials, and belongs to the technical field of concrete water reducing agents. The special admixture for solid waste-based cementitious materials comprises, by weight, 35 to 55 parts of component A of a specific molecular formula, 20 to 30 parts of component B of a specific molecular formula, and 10 to 40 parts of component C of a specific molecular formula. The long chain introduced into component A and component B of the present invention can enhance their dispersibility to powders, which is beneficial to improving the water reducing effect on solid waste-based cementitious materials; the phosphoric acid group contained in component C has a stronger adsorption capacity in several phases than carboxylic acid and sulfonic acid groups, and therefore can be preferentially adsorbed on the surface of tailings micropowder, thereby effectively avoiding the adsorption of tailings micropowder on water reducing agent and reducing the water reducing effect of water reducing agent. In addition, the lone pair of electrons of the N element contained in component C can chelate the CaO formed by the hydration of CaO in the steel slag. 2+ , slowing down the hydration rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete water reducing agents, and in particular relates to a special admixture for solid waste-based cementitious materials. Background Art

[0002] Since about 1 ton of carbon dioxide is emitted for every ton of cement produced, solid waste-based cementitious materials are increasingly being used in practical projects due to their low-carbon and environmentally friendly characteristics. However, due to the fine particle size of this material and the fact that it may also contain high-water-absorbing components such as tailings powder, traditional water-reducing agents are less suitable for this material, resulting in poor working performance of solid waste-based cementitious materials and concrete, large loss of slump and expansion over time, and other problems, limiting their application. In view of this situation, in order to better promote the application of solid waste-based cementitious materials, it is of great significance to develop a special admixture for solid waste-based cementitious materials. Summary of the invention

[0003] The object of the present invention is to provide a special admixture for solid waste-based cementitious materials.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention is to provide a special admixture for solid waste-based cementitious materials, which comprises, by weight, 35 to 55 parts of component A, 20 to 30 parts of component B and 10 to 40 parts of component C;

[0006] The molecular structure of the anion of component A is as follows, wherein n 1 The value range of n is 13 to 32. 2 The value range is 30 to 40:

[0007]

[0008] The molecular structure of the component B anion is as follows, wherein the value of n ranges from 40 to 50:

[0009]

[0010] The molecular structure of the component C anion is as follows, wherein the value of n ranges from 10 to 25:

[0011]

[0012] Preferably, the preparation steps of component A include:

[0013] The vinyl ether monomer, initiator and water are mixed, and then a mixed aqueous solution of methacrylic acid and sodium methacrylic sulfonate is added at the reaction temperature. After the addition is completed, the reaction is continued. After the reaction is completed, the pH value of the reaction system is adjusted to 6-7 to obtain component A.

[0014] More preferably, the mass ratio of vinyl ether monomer, methacrylic acid and sodium methacrylic acid sulfonate is 100:2.5-3.3:4.6-6.1; the amount of initiator added is 0.5-1.5% of the total mass of vinyl ether monomer, methacrylic acid and sodium methacrylic acid sulfonate; the molecular weight of the vinyl ether monomer is 2600-3400; the initiator is one or more combinations of hydrogen peroxide, sodium persulfate, azobisisobutyronitrile and azobisisoheptylnitrile.

[0015] More preferably, the reaction temperature is 70-90° C.; the adding time of the mixed aqueous solution of methacrylic acid and sodium methacrylic sulfonate is 120±5 min; and the continuing reaction time is 8-12 h.

[0016] Preferably, the preparation steps of component B include:

[0017] Polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride are mixed and reacted to obtain an intermediate; the intermediate, water and calcium lignin sulfonate are mixed and reacted to obtain component B.

[0018] More preferably, the mass ratio of polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride is 100:2:4-6;

[0019] The mixed reaction of polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride is carried out under an inert atmosphere, the temperature is raised to 70-100°C, and the temperature is kept for 5-7 hours;

[0020] The molecular weight of the intermediate is 2600-3200; the mass ratio of the intermediate, water and calcium lignin sulfonate is 100:50-100:15-20;

[0021] The intermediate, water and calcium lignin sulfonate are mixed and reacted under an inert atmosphere, the temperature is raised to 150-170° C., and the temperature is kept for 2-3 hours.

[0022] Preferably, the preparation steps of component C include:

[0023] L-aspartic acid, a catalyst and water are mixed for reaction, and the product is dried to obtain an intermediate; a sodium hydroxide solution with a mass fraction of 40-60% is prepared and added to a slurry prepared with the intermediate and water, and after the reaction is completed, a primary product of component C is obtained, and a mixture of phosphorous acid, formaldehyde and sulfuric acid is continuously added, and after the reaction is completed, the pH value of the system is adjusted to 5-7 to obtain component C.

[0024] More preferably, the catalyst is concentrated hydrochloric acid and / or concentrated phosphoric acid; the mass ratio of the L-aspartic acid to the catalyst is 100:10-25; the temperature of the mixed reaction of L-aspartic acid, the catalyst and water is 150-210° C., and the time is 5-12 hours.

[0025] More preferably, the mass ratio of the sodium hydroxide solution and the total water of the slurry to the intermediate and sodium hydroxide is 200-220:100:40-50;

[0026] The sodium hydroxide solution is added to the slurry for 0.5 to 1.5 hours, the temperature of the slurry is 50 to 80° C. when the sodium hydroxide solution is added, and the reaction is maintained at a constant temperature until the slurry becomes clear;

[0027] The mass ratio of the phosphorous acid, formaldehyde and sulfuric acid to the intermediate is 60-70:20-30:35-40:100. When the mixture of phosphorous acid, formaldehyde and sulfuric acid is added, the temperature of the component C primary product system is 100-120° C. The mixture is added dropwise in 60-90 minutes, and the reaction time after the addition is 10-15 hours.

[0028] The second technical solution of the present invention is to provide an application of the above-mentioned special admixture for solid waste-based cementitious materials in a water reducing agent.

[0029] The beneficial technical effects of the present invention are as follows:

[0030] Solid waste-based cementitious materials have fine particle sizes and contain high levels of CaO, amorphous Al-O and Si-O phases in components such as steel slag. Their negative effects on water reducers are mainly due to the formation of stable complexes between CaO or amorphous Al-O, Si-O and carboxyl or sulfonic acid groups, which results in the inability of the water reducer to be adsorbed on the surface of the cementitious material to achieve a dispersing effect. After the powders agglomerate, the water trapped inside cannot be released, and the water-reducing effect is greatly reduced.

[0031] Through XPS detection, the adsorption energies of several effective groups on the surfaces of different types of minerals were compared to determine the competitive adsorption effect, as shown in Table 1. Through the comparison of adsorption energies, it can be seen that the phosphate groups contained in component C have stronger adsorption capacity for several phases than the carboxylic acid and sulfonic acid groups in components A and B. Therefore, they can be preferentially adsorbed on the surface of tailings powder, thereby effectively avoiding the adsorption of tailings powder on components A and B. Under the synergistic effect of the three components, the water-reducing effect of the admixture is guaranteed. On the other hand, the N element contained in component C, whose lone pair of electrons can chelate the CaO formed by the hydration of CaO in the steel slag, 2+ , slowing down the hydration rate and improving its long-term working performance.

[0032] At the same time, the long chains introduced into component A and component B of the present invention can enhance their dispersibility for powders, which is beneficial to improving the water-reducing effect on solid waste-based cementitious materials and improving the working performance of concrete.

[0033] Table 1 Surface adsorption energies of phosphoric acid, carboxylic acid and sulfonic acid on several minerals

[0034] phase of matter CaO Amorphous Al-O Amorphous Si-O Phosphoric acid -2.23 -2.41 -3.20 carboxylic acid -1.89 -1.79 -2.85 Sulfonic acid -1.62 -1.56 -3.03 DETAILED DESCRIPTION

[0035] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0036] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] Example 1

[0040] The mass proportions of the components of the special admixture for solid waste-based cementitious materials are: 40 parts of component A, 25 parts of component B and 35 parts of component C;

[0041] The preparation process of component A is as follows:

[0042] Step 1: dissolve the vinyl ether macromonomer (molecular weight 2600) in deionized water, pour into a four-necked flask, and then add the initiator sodium persulfate, the initiator dosage is 0.5% of the total mass of the vinyl ether macromonomer, methacrylic acid, and sodium methacrylic sulfonate;

[0043] Step 2: preparing an aqueous solution of methacrylic acid and sodium methacrylic acid sulfonate in a certain mass ratio, so that the mass ratio of vinyl ether macromonomer: methacrylic acid: sodium methacrylic acid sulfonate is 100:2.5:5.0;

[0044] Step 3: Stir and heat the mixed solution in the four-necked flask using an oil bath, and maintain the temperature at 70°C; at the same time, slowly drip the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate into the four-necked flask using a separatory funnel, and the dripping of the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate is completed within 120min±5min; then continue to maintain the current temperature and stir to react for 8h;

[0045] Step 4: After the reaction is completed, adjust the pH of the solution to 6 with sodium hydroxide solution to obtain component A, n 1 The value is 16, n 2 The value is 33;

[0046] The preparation process of component B is as follows:

[0047] Polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride are mixed in a mass ratio of 100:2:4 and placed in a reaction kettle. After sealing, nitrogen is filled into the reaction kettle, and then the temperature is raised to 75° C. and the reaction is carried out at a constant temperature for 5 hours. After the reaction is completed, an intermediate is obtained.

[0048] Then, water and calcium lignin sulfonate were added into the reactor in a mass ratio of 100:55:15 among the intermediate, water and calcium lignin sulfonate, and then nitrogen was filled into the reactor, and the temperature was raised to 150° C. and the reaction was carried out at a constant temperature for 2 hours to obtain component B, and the n value was 42;

[0049] The preparation process of component C is as follows:

[0050] Step 1: Mix L-aspartic acid and deionized water and add them into a four-necked flask, connect a reflux and stirring device, and load a zeolite or a capillary tube; add concentrated hydrochloric acid as a catalyst in a ratio of 100:12 to the mass ratio of L-aspartic acid to the catalyst under stirring, and after the L-aspartic acid is completely dissolved, move the four-necked flask into an oil bath for heating, and turn on the cooling water at the same time;

[0051] Step 2: Raise the temperature to 150°C and keep the reaction for 6 hours; after the reaction is completed, cool to room temperature; then filter and wash the solid phase with deionized water for multiple times until the water used for washing is neutral; dry the solid phase at 105°C±5°C to constant weight to obtain an intermediate;

[0052] Step 3: weigh out three reagents according to the mass ratio of intermediate: sodium hydroxide: deionized water of 100:40:200; after preparing sodium hydroxide into a solution with a mass concentration of 40%, mix the remaining deionized water with the intermediate to prepare a slurry and transfer it to a four-necked flask; heat it to 50° C. in an oil bath with stirring, and then slowly drip the sodium hydroxide solution into the slurry with a separatory funnel, and keep the dripping time at 0.5h; keep the constant temperature reaction until the slurry becomes clear to obtain the initial product of component C;

[0053] Step 4: Continue to heat the system containing the initial product of component C in an oil bath pot, and keep the temperature at 100°C; prepare phosphorous acid, formaldehyde, and sulfuric acid solutions according to the mass ratio of intermediate, phosphorous acid, formaldehyde, and sulfuric acid of 100:60:20:35, and then drip into the system containing the initial product of component C under stirring, and the dripping time is about 64 minutes. After the dripping is completed, continue to maintain the temperature for 10 hours; after the reaction is completed, cool to room temperature, and adjust the pH to 5 with sodium hydroxide solution, so as to obtain component C, and the n value is 10.

[0054] Example 2

[0055] The mass proportions of the components of the special admixture for solid waste-based cementitious materials are: 35 parts of component A, 25 parts of component B and 40 parts of component C;

[0056] The preparation process of component A is as follows:

[0057] Step 1: dissolve the vinyl ether macromonomer (molecular weight 2900) in deionized water, pour into a four-necked flask, and then add initiator hydrogen peroxide, the initiator dosage is 1.0% of the total mass of the vinyl ether macromonomer, methacrylic acid, and sodium methacrylic acid sulfonate;

[0058] Step 2: preparing an aqueous solution of methacrylic acid and sodium methacrylic acid sulfonate in a certain mass ratio, so that the mass ratio of vinyl ether macromonomer: methacrylic acid: sodium methacrylic acid sulfonate is 100:2.8:5.5;

[0059] Step 3: Stir and heat the mixed solution in the four-necked flask using an oil bath, and maintain the temperature at 80°C; at the same time, slowly drip the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate into the four-necked flask using a separatory funnel, and the dripping of the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate is completed within 120min±5min; then continue to maintain the current temperature and stir to react for 11h;

[0060] Step 4: After the reaction is completed, adjust the pH of the solution to 6 with sodium hydroxide solution to obtain component A, n 1 The value is 19, n 2 The value is 36;

[0061] The preparation process of component B is as follows:

[0062] Polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride are mixed in a ratio of 100:2:5 by mass and placed in a reaction kettle. After sealing, nitrogen is filled into the reaction kettle, and then the temperature is raised to 85° C. and the reaction is carried out at a constant temperature for 7 hours. After the reaction is completed, an intermediate is obtained.

[0063] Then, water and calcium lignin sulfonate were added into the reactor in a mass ratio of 100:75:18 among the intermediate, water and calcium lignin sulfonate, and then nitrogen was filled into the reactor, and the temperature was raised to 160° C. and the reaction was carried out at a constant temperature for 2.5 hours to obtain component B, and the n value was 44;

[0064] The preparation process of component C is as follows:

[0065] Step 1: Mix L-aspartic acid and deionized water and add them into a four-necked flask, connect a reflux and stirring device, and load a zeolite or a capillary tube; add concentrated hydrochloric acid as a catalyst in a ratio of 100:16 to the mass ratio of L-aspartic acid to the catalyst under stirring, and after the L-aspartic acid is completely dissolved, move the four-necked flask into an oil bath for heating, and turn on the cooling water at the same time;

[0066] Step 2: Raise the temperature to 170°C and keep the reaction for 9 hours; after the reaction is completed, cool to room temperature; then filter and wash the solid phase with deionized water for multiple times until the water used for washing is neutral; dry the solid phase at 105°C±5°C to constant weight to obtain an intermediate;

[0067] Step 3: weigh out three reagents according to the mass ratio of intermediate: sodium hydroxide: deionized water of 100:45:210; after preparing sodium hydroxide into a solution with a mass concentration of 50%, mix the remaining deionized water with the intermediate to prepare a slurry and transfer it to a four-necked flask; heat it to 70° C. in an oil bath with stirring, and then slowly drip the sodium hydroxide solution into the slurry with a separatory funnel, and keep the dripping time at 1 hour; keep the reaction at a constant temperature until the slurry becomes clear, and obtain the initial product of component C;

[0068] Step 4: Continue to heat the system containing the initial product of component C in an oil bath pot, and keep the temperature at 110°C; prepare phosphorous acid, formaldehyde, and sulfuric acid solutions according to the mass ratio of intermediate, phosphorous acid, formaldehyde, and sulfuric acid of 100:65:25:37, and then drip into the system containing the initial product of component C under stirring, and the dripping time is about 71 minutes. After the dripping is completed, continue to maintain the temperature for 13 hours; after the reaction is completed, cool to room temperature, and adjust the pH to 6 with sodium hydroxide solution, so as to obtain component C, and the n value is 16.

[0069] Example 3

[0070] The mass proportions of the components of the special admixture for solid waste-based cementitious materials are: 50 parts of component A, 30 parts of component B and 20 parts of component C;

[0071] The preparation process of component A is as follows:

[0072] Step 1: dissolve the vinyl ether macromonomer (molecular weight 3100) in deionized water, pour into a four-necked flask, and then add the initiator azobisisoheptanenitrile, the initiator dosage being 1.3% of the total mass of the vinyl ether macromonomer, methacrylic acid, and sodium methacrylic acid sulfonate;

[0073] Step 2: preparing an aqueous solution of methacrylic acid and sodium methacrylic acid sulfonate in a certain mass ratio, so that the mass ratio of vinyl ether macromonomer: methacrylic acid: sodium methacrylic acid sulfonate is 100:3.1:5.9;

[0074] Step 3: Stir and heat the mixed solution in the four-necked flask using an oil bath, and maintain the temperature at 85°C; at the same time, slowly drip the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate into the four-necked flask using a separatory funnel, and the dripping of the mixed solution of methacrylic acid and sodium methacrylic acid sulfonate is completed within 120min±5min; then continue to maintain the current temperature and stir to react for 9h;

[0075] Step 4: After the reaction is completed, adjust the pH of the solution to 7 with sodium hydroxide solution to obtain component A, n 1 The value is 26, n 2 The value is 38;

[0076] The preparation process of component B is as follows:

[0077] Polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride are mixed in a mass ratio of 100:2:6 and placed in a reaction kettle. After sealing, nitrogen is filled into the reaction kettle, and then the temperature is raised to 90° C. and the reaction is carried out at a constant temperature for 5 hours. After the reaction is completed, an intermediate is obtained.

[0078] Then, water and calcium lignin sulfonate were added into the reactor in a mass ratio of 100:100:19 among the intermediate, water and calcium lignin sulfonate, and then nitrogen was filled into the reactor, and the temperature was raised to 165° C. and the reaction was carried out at a constant temperature for 3 hours to obtain component B, and the n value was 49;

[0079] The preparation process of component C is as follows:

[0080] Step 1: Mix L-aspartic acid and deionized water and add them into a four-necked flask, connect a reflux and stirring device, and load a zeolite or a capillary tube; add a catalyst (a 1:1 mixture of concentrated hydrochloric acid and concentrated phosphoric acid) at a mass ratio of L-aspartic acid to catalyst of 100:18 under stirring, and after the L-aspartic acid is completely dissolved, move the four-necked flask into an oil bath for heating, while turning on the cooling water;

[0081] Step 2: Raise the temperature to 210°C and keep the reaction for 11 hours; after the reaction is completed, cool to room temperature; then filter and wash the solid phase with deionized water for multiple times until the water used for washing is neutral; dry the solid phase at 105°C±5°C to constant weight to obtain an intermediate;

[0082] Step 3: weigh out three reagents according to the mass ratio of intermediate: sodium hydroxide: deionized water of 100:49:215; after preparing sodium hydroxide into a solution with a mass concentration of 60%, mix the remaining deionized water with the intermediate to prepare a slurry and transfer it to a four-necked flask; heat it to 80° C. in an oil bath with stirring, and then slowly drip the sodium hydroxide solution into the slurry with a separatory funnel, and keep the dripping time at 1 hour; keep the reaction at a constant temperature until the slurry becomes clear, and obtain the initial product of component C;

[0083] Step 4: Continue to heat the system containing the initial product of component C in an oil bath pot, and keep the temperature at 115°C; prepare phosphorous acid, formaldehyde, and sulfuric acid solutions according to the mass ratio of intermediate, phosphorous acid, formaldehyde, and sulfuric acid of 100:70:30:40, and then drip into the system containing the initial product of component C under stirring, and the dripping time is about 80 minutes. After the dripping is completed, continue to maintain the temperature for 11 hours; after the reaction is completed, cool to room temperature, and adjust the pH to 7 with sodium hydroxide solution, so as to obtain component C, and the n value is 23.

[0084] Comparative Example 1

[0085] Preparation of special admixtures for solid waste-based cementitious materials:

[0086] The method is the same as the preparation method of component A in Example 1.

[0087] Comparative Example 2

[0088] Preparation of special admixtures for solid waste-based cementitious materials:

[0089] The method is the same as the preparation method of component B in Example 1.

[0090] Comparative Example 3

[0091] Preparation of special admixtures for solid waste-based cementitious materials:

[0092] The method is the same as the preparation method of component C in Example 1.

[0093] The solid waste-based cementitious material admixture was used to replace the ordinary polycarboxylic acid admixture, and the preparation, curing and working performance of the concrete were tested according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". The mechanical properties of the concrete were tested according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The concrete prepared with ordinary admixtures was used as a control group and compared with the embodiment. The concrete mix proportions and test results of each experimental group are shown in Table 2 and Table 3, respectively.

[0094] Table 2 Concrete experimental mix ratio (kg / m 3 )

[0095]

[0096] Table 3 Test results of each experimental group

[0097]

[0098]

[0099] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A special admixture for solid waste-based cementitious materials, characterized in that: The components include, by mass, 35 to 55 parts of component A, 20 to 30 parts of component B and 10 to 40 parts of component C; The molecular structure of the component A anion is as follows, wherein the value range of n1 is 13 to 32, and the value range of n2 is 30 to 40: The molecular structure of the component B anion is as follows, wherein the value of n ranges from 40 to 50: The molecular structure of the component C anion is as follows, wherein the value of n ranges from 10 to 25:

2. The special admixture for solid waste-based cementitious materials according to claim 1, characterized in that: The preparation steps of component A include: The vinyl ether monomer, initiator and water are mixed, and then a mixed aqueous solution of methacrylic acid and sodium methacrylic sulfonate is added at the reaction temperature. After the addition is completed, the reaction is continued. After the reaction is completed, the pH value of the reaction system is adjusted to 6-7 to obtain component A.

3. The special admixture for solid waste-based cementitious materials according to claim 2, characterized in that: The mass ratio of vinyl ether monomer, methacrylic acid and sodium methacrylic acid sulfonate is 100:2.5-3.3:4.6-6.1; the added amount of the initiator is 0.5-1.5% of the total mass of the vinyl ether monomer, methacrylic acid and sodium methacrylic acid sulfonate; the molecular weight of the vinyl ether monomer is 2600-3400; the initiator is one or more combinations of hydrogen peroxide, sodium persulfate, azobisisobutyronitrile and azobisisoheptylnitrile.

4. The special admixture for solid waste-based cementitious materials according to claim 2, characterized in that: The reaction temperature is 70-90° C.; the adding time of the mixed aqueous solution of methacrylic acid and sodium methacrylic sulfonate is 120±5 min; and the continuing reaction time is 8-12 h.

5. The special admixture for solid waste-based cementitious materials according to claim 1, characterized in that: The preparation steps of component B include: Polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride are mixed and reacted to obtain an intermediate; the intermediate, water and calcium lignin sulfonate are mixed and reacted to obtain component B.

6. The special admixture for solid waste-based cementitious materials according to claim 5, characterized in that: The mass ratio of polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride is 100:2:4-6; The mixed reaction of polyethylene glycol 2000, concentrated sulfuric acid and maleic anhydride is carried out under an inert atmosphere, the temperature is raised to 70-100°C, and the temperature is kept for 5-7 hours; The molecular weight of the intermediate is 2600-3200; the mass ratio of the intermediate, water and calcium lignin sulfonate is 100:50-100:15-20; The intermediate, water and calcium lignin sulfonate are mixed and reacted under an inert atmosphere, the temperature is raised to 150-170° C., and the temperature is kept for 2-3 hours.

7. The special admixture for solid waste-based cementitious materials according to claim 1, characterized in that: The preparation steps of component C include: L-aspartic acid, a catalyst and water are mixed for reaction, and the product is dried to obtain an intermediate; a sodium hydroxide solution with a mass fraction of 40-60% is prepared and added to a slurry prepared with the intermediate and water, and after the reaction is completed, a primary product of component C is obtained, and a mixture of phosphorous acid, formaldehyde and sulfuric acid is continuously added, and after the reaction is completed, the pH value of the system is adjusted to 5-7 to obtain component C.

8. The special admixture for solid waste-based cementitious materials according to claim 7, characterized in that: The catalyst is concentrated hydrochloric acid and / or concentrated phosphoric acid; the mass ratio of the L-aspartic acid to the catalyst is 100:10-25; the temperature of the mixed reaction of the L-aspartic acid, the catalyst and water is 150-210° C., and the time is 5-12 hours.

9. The special admixture for solid waste-based cementitious materials according to claim 7, characterized in that: The mass ratio of the sodium hydroxide solution and the total water of the slurry to the intermediate and sodium hydroxide is 200-220:100:40-50; The sodium hydroxide solution is added to the slurry for 0.5 to 1.5 hours, the temperature of the slurry is 50 to 80° C. when the sodium hydroxide solution is added, and the reaction is maintained at a constant temperature until the slurry becomes clear; The mass ratio of the phosphorous acid, formaldehyde and sulfuric acid to the intermediate is 60-70:20-30:35-40:

100. When the mixture of phosphorous acid, formaldehyde and sulfuric acid is added, the temperature of the component C primary product system is 100-120° C. The mixture is added dropwise in 60-90 minutes, and the reaction time after the addition is 10-15 hours.

10. Use of the special admixture for solid waste-based cementitious materials according to any one of claims 1 to 9 in a water reducing agent.

Citation Information

Patent Citations

  • Air entraining type poly carboxylic acid high performance water reducing agent and preparation method thereof

    CN102951865A

  • Inorganic super setting retarder and preparing method and application thereof

    CN106316186A